IgG subclasses, specific antibodies and immunoglobulin allotypes in children with invasive Haemophilus influenzae type B and Staphylococcus aureus infections - Goddard, Elizabeth Anne (Department of Paediatrics and Child Health, 2018)
OBJECTIVE: The principal objective of this study was to measure various aspects of immunity in children with invasive infections due to Haemophilus influenzae type b and Staphylococcus aureus. These serious infections are a significant cause of childhood morbidity and mortality in all populations and affect healthy as well as compromised children. Evidence suggests that imbalances or deficiencies in certain aspects of immunity such as IgG subclasses, the capacity to make specific subclass antibodies, antibody affinities, complement isotypes, immunoglobulin allotypes or mannose binding protein may place certain children at risk for developing invasive disease. Investigation of these factors in a group of children with infection necessitated that normal ranges be established for children of comparable ages from the same population. A secondary objective of this study has therefore been to establish normal percentiles for the IgG subclasses in age, race and sex matched healthy controls. METHODS: Patients admitted to the Red Cross War Memorial Children's Hospital with septic meningitis due to Haemophilus influenzae type b and osteomyelitis/septic arthritis due to Haemophilus influenzae type b or Staphylococcus aureus formed the study population. Section A of this thesis describes the methods for establishing, validating and standardizing ELISAs for measuring the IgG subclasses (lgGl, IgG2, IgG3 and IgG4) and subclass antibodies specific to Haemophilus influenzae polyribosylribitol phosphate, Staphylococcus aureus teichoic acid and tetanus toxoid. The relative affinity of antibodies in these ELISAs was determined by the incorporation of diethylamine (DEA). In order to determine the immunoglobulin allotypes ELISAs were developed to measure the G1m(f), G2m(n) and Km(3) allotypes. The frequency of these allotypic markers in the different ethnic groups was established. The relationship between immunoglobulin allotypes and IgG subclass values were investigated in both patient and control groups. RESULTS: ELISA assays to measure IgG subclasses; IgG, IgG 1 and IgG4 tetanus toxoid antibodies; IgG, IgG 1 and IgG2 H. influenzae type b polyribosylribitol phosphate capsular polysaccharide antibodies; IgG, IgG1 and IgG2 S. aureus teichoic acid antibodies and G1m(f), G2m(n) and Km(3) allotypes were successfully established. Where possible the assays were standardized with reference sera and specimens were exchanged with international laboratories. Age, race and sex related percentile charts and tables of normal ranges for IgG and IgG subclasses of Black and Coloured children were established. The IgG and IgG 1 values were higher than those previously reported for children in developed countries. Black children with H. influenzae meningitis had significantly lower IgG 1, IgG2 and IgG3 levels compared to the controls and although similar trends were seen for IgG and IgG4 levels they were not statistically significant. Coloured children with H. influenzae meningitis and Coloured and Black children with H. influenzae osteomyelitis/septic arthritis also showed a similar tendency of lower IgG and IgG subclass levels than the controls but these trends were also not significantly different. All patients responded to tetanus toxoid antigen suggesting normal immunocompetence to protein antigens. H. influenzae type b capsular polysaccharide antibodies were low in children with H. influenzae type b meningitis and osteomyelitis/septic arthritis and did not increase during the illness. IgG and IgG 1 teichoic acid antibodies were raised in patients with S. aureus osteomyelitis/septic arthritis although no further rise in these antibodies was seen when measured several weeks after the illness. The antibody affinity ELISAs showed that IgG 1 tetanus toxoid antibody had a greater affinity than IgG4 tetanus toxoid antibody, the IgG 1 and IgG2 H. influenzae capsular polysaccharide antibodies were of similar affinity and the IgG 1 teichoic acid antibody was of higher affinity than the IgG2 antibody. The G1m(f) and G2m(n) positive allotypes were uncommon in Black but common in the Coloured populations whereas Km(3) was common in both groups. There was a significantly decreased frequency of the G2m(n) positive allotype in Coloured patients with H. influenzae type b meningitis and H. influenzae type b osteomyelitis/septic arthritis which was not found in patients with S. aureus osteomyelitis/septic arthritis. In both Coloured and Black children with H. influenzae meningitis there was a significantly decreased frequency of the Km(3) allotype. No differences in C4 isotypes and mannose binding protein levels were evident in the patient and control groups. CONCLUSION: This study has developed simple, specific and reproducible ELISAs to measure IgG subclasses and subclass antibodies specific to tetanus toxoid, H. influenzae polyribosylribitol phosphate and S. aureus teichoic acid. Age, sex and race related normal ranges for IgG subclasses in the local Black and Coloured populations have been established. Black children with H. influenzae type b meningitis had significantly lower IgG 1, IgG2 and IgG3 levels compared to the controls. There was a clear association between a decrease of the G2m(n) allotype and the Km(3) allotype and susceptibility to invasive infections caused by H. influenzae.